Overseas Employment and Remittance: Exploring the Nexus in the Context of Bangladesh (Global Journal of Management and Business Research, 2017)
countries and it is now one of the salient remittance gaining countries in Asia. With a few exceptions, manpower export has been showing increasing trend year by year. Most of the expatriates, who are largely unskilled, are working in the Middle East countries and in the UK and the USA. Like overseas employment, remittances flow has been increasing every year with its increased share in GDP and becomes vital elements for accelerating economic growth in Bangladesh. In this study, In addition to exploring current trend of migration & remittance inflows, we investigate whether there is any significant relationship between inflows of foreign remittances and overseas employment. We also made an effort to identify some barriers that impedes overseas employment and remittance earnings and considering these aspects, we suggest some recommendations that can gear our remittance earnings. Our analysis reveals that the relationship between remittance earning and overseas employment is statistically significant.
Keywords: migration; employment; overseas; remittance; obstacles; development